Republic of Latvia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper assesses whether Latvia's strategy to enter ERM2 and adopt the euro is appropriate. The paper examines the possibility of an exchange rate misalignment from various perspectives. It considers different notions of the real effective exchange rate and competitiveness; deviations of the exchange rate from statistically defined equilibrium concepts; and the possibility that central bank foreign exchange interventions have maintained the exchange rate artificially away from equilibrium. The paper finds little evidence of a major misalignment. The paper also analyzes modeling inflation in Latvia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet